Durable Complete Response to Alectinib in a Lung Adenocarcinoma Patient With Brain Metastases and Low-Abundance EML4-ALK Variant in Liquid Biopsy: A Case Report - Zhu, Yingying; Jia, Ran; Shao, Yang W.; Zhu, Liuqing; Ou, Qiuxiang; Yu, Man; Wu, Xue; Zhang, Yanbei (Frontiers in Oncology, 2020)
EML4-ALK fusions are targetable oncogenic drivers in a subset of advanced non-small cell lung cancer (NSCLC) patients that can benefit from selected ALK inhibitors. Precise detection of ALK fusions may yield critical information for selection of appropriate therapy and hence improve patient survival. Analysis of circulating tumor DNA (ctDNA) in liquid biopsies using next generation sequencing (NGS) prior to or during treatment hold great promise for disease monitoring and treatment guidance of various cancers including NSCLC. Herein, we report a case of a 21-year-old advanced lung adenocarcinoma patient with a low abundance (0.03%) of EML4-ALK rearrangement identified in plasma ctDNA upon progression on two lines of chemotherapy that demonstrated long-term complete response to alectinib (>13 months) including metastatic brain tumors. Patient’s clinical and pathologic characteristics, computerized tomography (CT) scans and brain magnetic resonance imaging (MRI) were reviewed retrospectively. Taken together, our report not only reinforces the translational utility of NGS-based genomic sequencing of liquid biopsy in guiding clinical practice, but also highlights the superior efficacy of alectinib than chemotherapy in ALK+ NSCLC with brain metastases, albeit at a low variant allele abundance.